Using the Mertens' theorem for Cauchy products we know that the Cauchy product of series $$ \sum_{n=0}^{\infty}\frac{(-1)^{n+1}}{n+1}\qquad\text{and}\qquad\sum_{n=0}^{\infty}\frac{1}{3^n} $$ does converge. But how can we try to find the value of this sum?

What I only know is that we can write that this sum equals to $$ S=\sum_{n=0}^{\infty}c_n\qquad\text{where}\qquad c_n=\sum_{k=0}^{n}\frac{1}{3^{n-k}}\frac{(-1)^{k+1}}{k+1} $$ but I'm not able to find any way to calculate the sum. Any hints?

  • 5
    $\begingroup$ If I understand correctly, by MERTENS' Theorem, $S$ is equal to the product of the of the initial sums, right? The first is $-\ln(2)$ and the second is $\frac{3}{2}$ by the geometric series. $\endgroup$
    – Ramanujan
    Dec 23 '18 at 12:38
  • 1
    $\begingroup$ Yes but how to find it using only the definition of Cauchy product of series? $\endgroup$
    – avan1235
    Dec 23 '18 at 12:44
  • $\begingroup$ If you were presented with this sum as a $S$ and asked to evaluate it. I would think that decomposing it (via cauchy product) would be the easiest way of coming to a conclusion. $\endgroup$
    – Mason
    Dec 23 '18 at 16:11

Here is my "lengthy" solution (elaborating @ViktorGlombik comment). Let's start with your sum:




where $\Phi(a,b,c)$ is so-called Lerch transcendent.

Also there is one useful identity: $\Phi(-3, 1, n+2) = \frac{1}{\Gamma(1)}\int_0^\infty\frac{e^{-(n+2)t}}{1+3e^{-t}}dt$.

By substitution $u=1+3e^{-t}$ (and $\Gamma(1) = 1$), this integral leads to

$$\Phi(-3, 1, n+2) = \frac{1}{3^{n+2}}\int_1^4 \frac{(u-1)^{n+1}}{u} du.$$

Plugging it back (observe $u\in(1,4)$ for the convergence of the geometric series), we obtain: $$S=\sum_{n=0}^\infty\frac{1}{3^n}\left[(-3)^{n+1}\frac{1}{3^{n+2}}\int_1^4\frac{(u-1)^{n+1}}{u}du-\frac{2}{3}\log(2)\right]=$$ $$=\sum_{n=0}^\infty\frac{1}{3^{n+1}}\int_1^4\frac{(1-u)^{n+1}}{u}du-\log(2)=$$ $$=\int_1^4\frac{1}{u}\sum_{n=0}^{\infty}\left(\frac{1-u}{3}\right)^{n+1}du - \log(2)=$$ $$=\int_1^4\frac{1}{u}\frac{1-u}{u+2}du-\log(2)=-\frac{3}{2}\log(2)+\log(2)-\log(2)=-\frac{3}{2}\log(2).$$

So yes, indeed the sum converges to $S=-\frac{3}{2}\log(2)$.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.